Impacts of changes in land use and cover in the Municipality of Altamira, Pará (Research, Society and Development, 2020)
Due to the intended development from the landscape dynamics, and the construction of the Belo Monte Hydroelectric Plant, the urban space of Altamira has undergone major transformations in land cover. Therefore, this study aimed to classify and quantify the changes suffered in land use and cover in the urban micro-region of Altamira in the years 2010 and 2018. In the methodology, the online platform MapBiomas was used to classify and quantify the classes of use and coverage from the earth. The values of the samples were measured by the statistical calculator and the field calculator of the QGis 3.4.13 software. The software was used for qualitative and quantitative analyzes and for the generation of the final product (land use and land cover maps). The results showed that in 2010, the area occupied by forest formation extended for 23,631 km², while in 2018 it covered 26,081 km². It appears that urban infrastructure has increased considerably (71%). An important characteristic observed is the appearance of a new class in 2018, referring to the planting of annual and perennial crops, which can be associated with the new activities practiced, resulting from the population increase, and expansion of agricultural activity in the region. Therefore, the class that has undergone the greatest change in the central region of Altamira is that of urban infrastructure. It is possible to verify that the presence of new constructions such as the Transamazônica Highway and the Belo Monte hydroelectric power plant, caused a great change in the use and occupation of the region's soil, mainly regarding the urban fabric of the locality.